2021
DOI: 10.1016/j.cell.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine metabolism is a central determinant of helper T cell lineage fidelity

Abstract: Polyamine synthesis represents one of the most profound metabolic changes during T cell activation, but the biological implications of this are scarcely known. Here, we show that polyamine metabolism is a fundamental process governing the ability of CD4 + helper T cells (T H ) to polarize into different functional fates. Deficiency in ornithine decarboxylase, a crucial enzyme for polyamine synthesis, results in a severe failure of CD4 + T cells to adopt correct subset specification, underscored by ectopic expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 76 publications
(100 reference statements)
10
153
0
2
Order By: Relevance
“…Among them, polyamine synthesis is a marker of T cell activation and proliferation. Puleston et al reported that polyamine-hypusine deficiency leads to extensive epigenetic remodeling driven by altered histone acetylation and a re-wired tricarboxylic acid (TCA) cycle, which has an impact on the ability of CD4 + helper T cells to differentiate into different functional fates (102). Accumulating evidence suggests that metabolism affects cell signaling and epigenetics, thereby controlling the lifespan of T cells and converting T cells to an exhaustion state, which inhibits effector function and leads to adverse effects on immune checkpoint molecules (ICM) targeted therapies.…”
Section: Metabolic Dysregulations Are Linked To Epigenetic Changes In...mentioning
confidence: 99%
“…Among them, polyamine synthesis is a marker of T cell activation and proliferation. Puleston et al reported that polyamine-hypusine deficiency leads to extensive epigenetic remodeling driven by altered histone acetylation and a re-wired tricarboxylic acid (TCA) cycle, which has an impact on the ability of CD4 + helper T cells to differentiate into different functional fates (102). Accumulating evidence suggests that metabolism affects cell signaling and epigenetics, thereby controlling the lifespan of T cells and converting T cells to an exhaustion state, which inhibits effector function and leads to adverse effects on immune checkpoint molecules (ICM) targeted therapies.…”
Section: Metabolic Dysregulations Are Linked To Epigenetic Changes In...mentioning
confidence: 99%
“…In addition to being epigenetic, T cell subset activation and differentiation are highly dependent on metabolic status [ 240 , 241 ], which is crucial for their antitumor functions. Recently, the CTLA-4 blockade has been shown to promote metabolic fitness and the infiltration of immune cells, especially in glycolysis-low tumors where tumor-specific CD8 + T cell responses correlated with phenotypic and functional destabilization of Tregs towards IFN-γ and TNF-α-producing cells in the tumor in mice model [ 242 ].…”
Section: Prospects Of Combining Therapies For Cd4 + T Cell Harnessingmentioning
confidence: 99%
“…In the setting of GVHD, Tc17 cells were found to express high levels of multiple prototypic lineagedefining transcription factors (TFs) (e.g., RORgt and T-bet) and cytokines (e.g., IL-17A, IL-22, IFN-g, granulocyte-macrophage colony-stimulating factor (GM-CSF), and IL-13) (93). A recent study may provide an explanation for this cross talk: Puleston et al found that CD4 + helper T-cell lineage fidelity is governed by polyamine metabolism, and polyamine-deficient T cells showed severe deficiency to adopt correctly selected subsets, resulting in the simultaneous expression of multiple lineage-defining TFs and cytokines (94).…”
Section: Distinct Sensitivity Of Th Subsets and Cytokine Pathways To ...mentioning
confidence: 99%